2004
DOI: 10.1212/01.wnl.0000130530.55104.b5
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesions impair frontal lobe function regardless of their location

Abstract: Objective-To analyze the effect of white matter lesions in different brain regions on regional cortical glucose metabolism, regional cortical atrophy, and cognitive function in a sample with a broad range of cerebrovascular disease and cognitive function.Methods-Subjects (n = 78) were recruited for a study of subcortical ischemic vascular disease (SIVD) and Alzheimer disease (AD) contributions to dementia. A new method was developed to define volumes of interest from high-resolution three-dimensional T1-weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
352
4
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(409 citation statements)
references
References 43 publications
40
352
4
13
Order By: Relevance
“…We and others have previously reported cross‐sectional associations of WMH with cognition, most notably perceptual speed and executive functions, and WMH are generally thought to have a relatively domain‐specific effect on cognition 11, 12, 21. In this study, we again observed that the impact of WMH on the initial level of cognition was domain specific, affecting perceptual speed only.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We and others have previously reported cross‐sectional associations of WMH with cognition, most notably perceptual speed and executive functions, and WMH are generally thought to have a relatively domain‐specific effect on cognition 11, 12, 21. In this study, we again observed that the impact of WMH on the initial level of cognition was domain specific, affecting perceptual speed only.…”
Section: Discussionsupporting
confidence: 73%
“…The degree to which WMH contribute to progressive cognitive decline among older persons initially free of cognitive impairment also is poorly understood. Cross‐sectional studies have shown that WMH are associated with subtle cognitive decrements, particularly in perceptual speed and executive functions,10, 11, 12 but little data are available on the relation of WMH with cognitive decline among persons initially free of cognitive impairment 7, 13, 14, 15, 16. A better understanding of the degree to which WMH increase the risk of MCI and contribute to progressive decline in multiple cognitive systems is needed to facilitate strategies to promote cognitive health in old age.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the strong convergence of white matter fibers in the frontal lobes may explain why lesions in any region of the brain tend to show a proportionally robust effect in this broad associative cortical area. [33] The precuneus seems to be involved in modulating consciousness via corticosubcortical connections that include the thalamus. [26,34] The proper activation of the precuneus has been considered to be critical in the recovery of low-level states of consciousness and has been considered to be a key player in the default mode network.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the loss of connectivity between the precuneus and the frontal or temporal areas has been associated with autism and cognitive impairment with a high risk of developing Alzheimer`s disease, respectively. [33] It is now assumed that brain functions, from the basic mechanism that regulates consciousness to the most complex cognitive processes, are not located in specific brain areas of isolated functioning but occur via intricate neural connections underlying the dynamic interactions between brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Bowley et al (2010) and many others (Feldman and Peters 1998;Peters and Sethares 2002;Sandell and Peters 2003) have reported an age-related accumulation of myelin defects and axon loss in forebrain white matter pathways of the rhesus monkey (e.g., the corpus callosum and cingulum bundle, anterior commissure). Additionally, others have shown age-related loss of white matter volume in MRI (Guttmann et al 1998;Wisco et al 2008), increases in white matter hyperintensities in MRI (Tullberg et al 2004;Wakefield et al 2010) and increased myelin damage inferred by loss of fractional anisotropy from diffusion tensor imaging (DTI; Makris et al 2007). As myelin defects accumulate with age, it is likely that microglia would be activated and participate in the clearance of damaged white matter and axons.…”
Section: Microglial Activation and Phagocytosis Throughout The Lifespanmentioning
confidence: 99%